Implementasi Akad Qardh pada Transaksi Utang Piutang di Bank Sedekah Nurul Falah Al-Mubarok Kabupaten Bekasi - Agustine, Hendra Karunia; Mashudi, Yudi; Fadiyah, Afifatul (Al Barakat, 2025)
Sedekah Nurul Falah Al-Mubarok Bank appeared to provide account receivable transaction facilities based on qardh agreement sourced from the alms funds of its members. However, there are issues regarding the suitability of the agreement used with sharia principles. This study aims to determine and analyze the implementation of the qardh agreement in account receivable transaction at Nurul Falah Al-Mubarok charity bank in Bekasi regency based on the principles of Islamic law (fiqh muamalah). The method used was a qualitative approach with a case study. The main sources of data and information were obtained through in-depth interviews with administrators, members, foundation advisors, and religious leaders. The results of this study showed that this charity bank applies the concept of "from members, by members, for members," which is in line with the principle of al-Muslimuna Ala Syurutihim. The mechanism of account receivable transaction includes loan applications by members, installment agreements, and relief policies in the form of extensions or write-offs for members who experience difficulties. Funds are collected using a tabarru agreement, while the implementation of the qardh agreement consists of three stages, namely Completing the administration, The qardh agreement process, The loan repayment process. The results of the study showed that the practice of qardh agreement in account receivable transactions at this charity bank has generally fulfilled its pillars and requirements and avoids any additional costs (interest) on repayment, thus indicating that the qardh agreement applied is free from elements of maisir, gharar, and riba because it is in accordance with Islamic law and has been determined to be in accordance with sharia rules in the fatwa of the Indonesian Ulema Councils National Sharia Board (DSN-MUI) No. 19/DSN-MUI/IV/2001 concerning Al-Qardh.